Anti-Cryptosporidial Drug-Discovery Challenges and Existing Therapeutic Avenues: A “One-Health” Concern - Munwar Ali; Chang Xu; Shah Nawaz; Ahmed Ezzat Ahmed; Qazal Hina; Kun Li (Life, 2024)
Cryptosporidiosis is the leading cause of life-threatening diarrheal infection, especially in infants. Oocysts contaminate the environment, and also, being a zoonotic disease, cryptosporidiosis is a threat to One Health. Nitazoxanide is the only FDA-approved drug, effective only in immunocompetent adults, and is not safe for infants. The absence of mitochondria and apicoplast, the presence of an electron-dense band (ED band), hindrances in its genetic and phenotypic manipulations, and its unique position inside the host cell are some challenges to the anti-cryptosporidial drug-discovery process. However, many compounds, including herbal products, have shown efficacy against Cryptosporidium during in vitro and in vivo trials. Still, the “drug of choice” against this protozoan parasite, especially in immunocompromised individuals and infants, has not yet been explored. The One-Health approach addresses this issue, focusing on the intersection of animal, human, and environmental health. The objective of this review is to provide knowledge about novel anti-cryptosporidial drug targets, available treatment options with associated limitations, and possible future shifts toward natural products to treat cryptosporidiosis. The current review is organized to address the treatment and prevention of cryptosporidiosis. An anti-cryptosporidial drug that is effective in immunocompromised individuals and infants is a necessity of our time.